Ab initio quantum study of UV absorption spectra of cis- and trans-hexatriene - Komainda, Adrian; Zech, Alexander; Köppel, Horst (Journal of molecular spectroscopy, 2015)
The vibronic structure of the UV-absorption spectra of cis- and trans-hexatriene is revisited in a comparative theoretical investigation. The multidimensional potential energy surfaces of the relevant 1A1 (1Ag) and 1B2 (1Bu) electronic states are obtained from CASPT2 and MRCI ab initio calculations using carefully chosen CAS-spaces. These provide the basis for subsequent wavepacket dynamical calculations for the coupled electronic states carried out with the multiconfiguration time-dependent Hartree scheme. The experimental spectra in the ∼5eV energy range are well reproduced for both isomers. The influence of the various degrees of freedom is assessed by comparing the results for different dimensionalities of the calculations. The implications of these findings for the photophysical properties (fluorescence dynamics) are discussed.
Gesehen am 15.07.2020